Treatment of fish wastewater by using water spinach (ipomoea aquatica) in an aquaponic system - Siti Nor Azira , Mahmood @ Che Mood (2013)
An aquaponic systein was designed to investigate the effect of HRT towards water quality. Water spinach (Ipomoea Aquatica) was cultivated in medium growth bed to examine for its ability to remove nutrients from aquaculture wastewater. The effectiveness of quantity of water spinach also investigated in this project to see how does the number of water spinaches affect the contaminated water. The plants were fed wastewater from Catfish (Pangasius Sutchi) production facility. The aquaponic system was investigated in 2-, 4- and 6-d hydraulic retention times (HRTs) with particular emphasis on nitrogen conversion and removal through the system. Although substantial amounts of soluble and insoluble substances were released by the roots accommodation, the plants were able to remove the pollutants in wastewater. Both BOD 5 and COD removals were enhanced by the longer HRT as well as the decreasing of concentration of NH 3-N, NO 3 -N, and NO 2 -N. The present findings highlight the effectiveness of water spinach and the HRT in improving the pollutant removals in the aquaponic system.